Elucidation of the pramanicin biosynthetic pathway reveals a DUF2306 family membrane protein involved in terminal epoxidation - Gao, Yang-Le; Chen, Wei; Zhang, Jing-Jing; Li, Pei-Lin; Li, Li; Zhang, Hui (Frontiers in Microbiology, 2026)
Pramanicin is a fungal metabolite with notable biological activities, including antifungal and anticancer properties. While its chemical synthesis has been achieved, its biosynthetic pathway has remained elusive. Here, we report the identification of the pramanicin biosynthetic gene cluster from the fungus Macrophomina phaseolina. Heterologous expression in Aspergillus nidulans demonstrated that the hybrid polyketide-nonribosomal (PKS-NRPS) enzyme PraA synthesizes a linear precursor that cyclizes to form pre-pramanicin. The flavin-dependent monooxygenase PraD and short-chain dehydrogenase/reductase PraB subsequently catalyze a hydroxylation and ketoreduction to yield pramanicin-A. Notably, we established that the final epoxidation step requires the PraC—a membrane-integrated protein of the previously uncharacterized DUF2306 family. This represents the first functional assignment of a DUF2306 family protein in natural product biosynthesis. Combinatorial expression and in vivo feeding experiments confirmed that PraC is essential for the formation of the bioactive epoxide moiety in pramanicin. Our work deciphers the biosynthetic pathway of a pharmaceutically relevant natural product, expands the enzymatic toolbox for synthetic biology by characterizing a novel family of membrane-associated biosynthetic enzymes.